The use of modern information technologies for educational and methodological support of the Department of SCIA - Bilushchak, Tetiana; Bovtach, Kateryna (Видавництво Львівської політехніки, 2020)
A feasible analysis of the benefits of using the electronic catalog for educational and methodological support of the Department of SCIA.
Keywords: electronic catalog; database; information retrieval; information request; information technology